2018
DOI: 10.1021/jacs.8b12493
|View full text |Cite
|
Sign up to set email alerts
|

Mimicking Microbial Rhodopsin Isomerization in a Single Crystal

Abstract: Bacteriorhodopsin represents the simplest, and possibly most abundant, phototropic system requiring only a retinal-bound transmembrane protein to convert photons of light to an energygenerating proton gradient. The creation and interrogation of a microbial rhodopsin mimic, based on an orthogonal protein system, would illuminate the design elements required to generate new photoactive proteins with novel function. We describe a microbial rhodopsin mimic, created using a small soluble protein as a template, that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 44 publications
2
21
0
Order By: Relevance
“…The observation that while a PSB gives a 13- cis photoproduct, the rUSB gives rise to photoisomerization of the C15N bond is consistent with a recent study of a rhodopsin mimic variant of M2 . In this study, it was shown that an all - trans retinylidene can be photoisomerized to a stable 13- cis ,15- cis product; but only in its PSB state.…”
supporting
confidence: 90%
“…The observation that while a PSB gives a 13- cis photoproduct, the rUSB gives rise to photoisomerization of the C15N bond is consistent with a recent study of a rhodopsin mimic variant of M2 . In this study, it was shown that an all - trans retinylidene can be photoisomerized to a stable 13- cis ,15- cis product; but only in its PSB state.…”
supporting
confidence: 90%
“…We next investigated the potential of the DS trimer as a new protein design template by engineering a metal binding site as a proof of principle. The engineering of a metal‐binding site to control oligomerization and create new function has been previously investigated by several research groups including us [20,36,42–44] . Herein, we wanted to show how the structural differences between monomer, dimer, and trimer can be used to create a metal‐binding site by minimal changes into the protein sequence.…”
Section: Figurementioning
confidence: 99%
“…The engineering of a metal-binding site to control oligomerization and create new function has been previously investigated by several research groups including us. [20,36,[42][43][44] Herein, we wanted to show how the structural differences between monomer, dimer, and trimer can be used to create a metal-binding site by minimal changes into the protein sequence. A characteristic feature of the DS trimer is the pseudo C 3 symmetry axis running through a volume of buried surface unique to the trimer structure ( Figure S4a).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the designable proteins are relatively stable on limited mutations, allowing us to study the photoreaction mechanisms through systematical mutagenesis. Geiger, Borhan et al .have been working on the artificial rhodopsin mimics for a long history and have provided several mimics with the human proteins CRABPII or the cellular retinol binding protein II (CRBPII) as scaffoldings (10; 11; 12; 13). The crucial component for the photoreaction, the retinal Schiff base (RSB), is correctly generated in these mimics between the chromophore retinal and the sidechain of the residue LYS in the scaffolding protein.…”
Section: Introductionmentioning
confidence: 99%